Microsoft Excel 2016 Programming by Example : With VBA, XML, and ASP - Korol, Julitta (Mercury Learning and Information, 2017)
A practical, how-to book on Excel programming, suitable for readers already familiar with the Excel user interface, this book introduces programming concepts via numerous multi-step, illustrated, hands-on exercises. -- Edited summary from book.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets.; Visual programming (Computer science); elektronické knihy; electronic books